ANALYSIS OF FIGURATIVE LANGUAGE IN THE ADVERTISEMENT TAGLINES IN INDONESIA TATLER MAGAZINE - -, ZAKIYAH (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: figurative language, advertisement, Indonesia Tatler magazine. Figurative language is related to the aesthetic of words. The writer conducted a research about figurative language in the advertisement taglines in Indonesia Tatler magazine. This study is aimed to identify: (1) the kinds of figurative language found in some selected advertisement taglines in Indonesia Tatler magazine. (2) the meanings of the figurative language of some selected advertisement taglines found in Indonesia Tatler magazine.In  this research, the writer uses qualitative approach. The data source is Indonesia Tatler magazine August 2013 edition, the taglines of analysis are from advertisement in Indonesia Tatler magazine. There were several steps to collect the data: taking advertisement from Indonesia Tatler August 2013 edition, Selecting, listing, identifying advertisement taglines which contain figurative language related with theory of Keraf. The writer analyzed it trough the following steps identifying what kinds of figurative language used in the advertisement taglines with related theories, classifying the data and putting it into table, analyzing the meaning of the figurative language of some selected advertisement taglines.The writer selected 20 advertisement taglines from Indonesia Tatler magazine as the object of her research by using the theories of figurative language, connotative and denotative approach about style in language. The writer has been finding: alliteration, personification, hyperbole, metonymy, and climax. Personification is prefered to use in some advertisements in Indonesia Tatler magazine. Personification is assumed to be the most effective way than others, this figurative language can support and create an interesting meaning since it is reflecting human’s characteristics into the thing.The writer suggests that the next researchers conduct similar research about figurative language by using different point of view or objects. Moreover, the next researchers are able to find other theories concerning the idea of figurative language.